Detection Of Trace Heavy Metal Ions By Anodic Stripping Voltamettry Using L-Cysteine Functionalized Carbon Nanotubes Paste Electrode - Tan, Chin Wei (2012)
The development and application of the L-cysteine functionalized carbon nanotubes paste electrode (Cys-CNTPE) biosensor for the detection of lead ion (Pb2+) and cadmium ion (Cd2+) in the aqueous system are described. L-cysteine was covalently attached to multi-walled carbon nanotubes (MWCNTs) via N-(3-dimethylaminopropyl)-N′-ethylcarbodiimide-N-hydroxysuccinimide (EDC-NHS) carbodiimide coupling as a recognition element for its high metal-chelating ability towards Pb2+ and Cd2+. The covalent attachment of L-cysteine on MWCNTs was verified with the results from Fourier Transform Infrared Spectroscopy (FTIR) characterization.